THE INFLUENCE OF INFLUENCER MARKETING AND FOMO ON CONSUMER PURCHASE DECISIONS - Chandra, Ester (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study aims to investigate the influence of Influencer Marketing and Fear of Missing Out (FOMO) on consumer Purchase Decisions within the context of digital commerce in Indonesia. Grounded in the Stimulus–Organism–Response (S-O-R) theory, this research analyzes how external marketing stimuli affect internal psychological states and subsequent consumer behavior. The research adopts a quantitative approach, employing a purposive sampling technique with 100 active digital media users aged 18–40. Data were collected using an online survey with a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) via SmartPLS 3. The results indicate that Influencer Marketing has a significant and positive effect on FOMO and that FOMO, in turn, significantly influences Purchase Decision. However, FOMO does not mediate the relationship between Influencer Marketing and Purchase Decision. These findings imply that while Influencer Marketing effectively intensifies feelings of urgency, FOMO itself is insufficient as a standalone mechanism for converting influencer-driven engagement into actual purchases. The study concludes that Influencer Marketing acts as an important external trigger, and FOMO operates as an internal state, both shaping consumer behavior. To optimize marketing strategies, future research should investigate additional mediators and moderators, such as trust, product quality, and pricing, across diverse demographic and cultural contexts.